2020
DOI: 10.1107/s2053229620015041
|View full text |Cite
|
Sign up to set email alerts
|

Albofungin and chloroalbofungin: antibiotic crystals with 2D but not 3D isostructurality

Abstract: The potent antibiotics albofungin [systematic name: (1S,4R,8aR)-13-amino-1,15,16-trihydroxy-4-methoxy-12-methyl-3,4,8a,13-tetrahydro-1H-xantheno[4′,3′,2′:4,5][1,3]benzodioxino[7,6-g]isoquinoline-14,17(2H,9H)-dione, C27H24N2O9, 1] and its chlorinated analogue chloroalbofungin (the 11-chloro analogue, C27H23ClN2O9, 2) have been crystallized following their isolation from the bacterial strain Streptomyces chrestomyceticus and their structures determined by single-crystal X-ray diffraction. The novel N-aminoquinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Albofungins were isolated and purified as previously described ( She et al, 2021 ). The purity of tested compounds was confirmed by high-performance liquid chromatography (95% purity, HPLC, Waters 2695, Milford, MA, United States), and their structures were determined by the Bruker NMR spectrometers (Bruker, Billerica, MA, United States) and X-ray crystallography as previously described ( Ye et al, 2020 ; She et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albofungins were isolated and purified as previously described ( She et al, 2021 ). The purity of tested compounds was confirmed by high-performance liquid chromatography (95% purity, HPLC, Waters 2695, Milford, MA, United States), and their structures were determined by the Bruker NMR spectrometers (Bruker, Billerica, MA, United States) and X-ray crystallography as previously described ( Ye et al, 2020 ; She et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Albofungin and its derivatives were identified as secondary metabolites from various Streptomyces species, and they belong to polycyclic isoquinolone–xanthone family. Albofungin and chloroalbofungin have been crystallized and their structures were determined by single-crystal X-ray diffraction ( Ye et al, 2020 ). Our previous study has reported remarkable antibacterial activities against “ESKAPE pathogens” and antitumor activities of albofungin and its derivatives isolated from the bacterium S. chrestomyceticus BCC 24770 ( She et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that they shared a similar biosynthesis pathway with 3 and 4, 1 and 2 might reasonably possess the same stereochemistry as 3 and 4. The absolute configurations of 3 and 4 were established as 10-S, 13-R, and 19-R by using the X-ray crystallographic analysis in our previous study (Ye et al, 2020). The circular dichroism experiment was conducted to verify the stereochemistry of 1 and 2.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…Streptomycetes are the most chemically studied actinobacteria and proven to have an extraordinary ability to produce colored polycyclic xanthones ( Winter et al, 2013 ). Currently, their fermentation broths were frequently extracted with an equal volume of ethyl acetate three times to obtain the crude extracts ( Hu et al, 2019 ; Xu et al, 2020 ; Ye et al, 2020 ; She et al, 2021 ). Further isolation and identification procedure might be hardly hindered by the low solubility of this kind of pigments in many organic solvents ( Nakagawa et al, 1986 ; Hu et al, 2020 ), and chemical modification by acetylation or methylation could be used as a solution to address this problem ( Ömura et al, 1986 ).…”
Section: Isolation and Identificationmentioning
confidence: 99%